Detection of phenotype‐specific therapeutic vulnerabilities in breast cells using a CRISPR loss‐of‐function screen. Issue 8 (1st May 2021) - Barkovskaya, Anna; Goodwin, Craig M.; Seip, Kotryna; Hilmarsdottir, Bylgja; Pettersen, Solveig; Stalnecker, Clint; Engebraaten, Olav; Briem, Eirikur; Der, Channing J.; Moestue, Siver A.; Gudjonsson, Thorarinn; Mælandsmo, Gunhild M.; et al.
Abstract : Cellular phenotype plasticity between the epithelial and mesenchymal states has been linked to metastasis and heterogeneous responses to cancer therapy, and remains a challenge for the treatment of triple‐negative breast cancer (TNBC). Here, we used isogenic human breast epithelial cell lines, D492 and D492M, representing the epithelial and mesenchymal phenotypes, respectively. We employed a CRISPR‐Cas9 loss‐of‐function screen targeting a 2240‐gene 'druggable genome' to identify phenotype‐specific vulnerabilities. Cells with the epithelial phenotype were more vulnerable to the loss of genes related to EGFR‐RAS‐MAPK signaling, while the mesenchymal‐like cells had increased sensitivity to knockout of G2 ‐M cell cycle regulators. Furthermore, we discovered knockouts that sensitize to the mTOR inhibitor everolimus and the chemotherapeutic drug fluorouracil in a phenotype‐specific manner. Specifically, loss of EGFR and fatty acid synthase (FASN) increased the effectiveness of the drugs in the epithelial and mesenchymal phenotypes, respectively. These phenotype‐associated genetic vulnerabilities were confirmed using targeted inhibitors of EGFR (gefitinib), G2 ‐M transition (STLC), and FASN (Fasnall). In conclusion, a CRISPR‐Cas9 loss‐of‐function screen enables the identification of phenotype‐specific genetic vulnerabilities that can pinpoint actionable targets and promising therapeutic combinations. Abstract : Phenotypic heterogeneity hampers anticancer treatment efficacy. Here, we applied a CRISPR‐Cas9 loss‐of‐function screen of a 'druggable genome' in isogenic breast cell lines displaying opposing EMT phenotypes. We identified phenotype‐specific genetic vulnerabilities (alone or under 'therapy pressure') that represent actionable targets in distinct phenotypes: EGFR‐MAPK signaling in the epithelial phenotype, and G2 ‐M transition and FASN in the mesenchymal phenotype cells.